Navigating the Debate on Managing Large (≥4 cm) Thyroid Nodules. (16th April 2022) - Steinmetz-Wood, Samantha N.; Kennedy, Amanda G.; Tompkins, Bradley J.; Gilbert, Matthew P.
Abstract : Purpose . Discordant practice guidelines for managing large thyroid nodules may result in unnecessary surgeries and costs. Recent data suggest similar false-negative rates in fine needle aspiration (FNA) biopsies between small (<4 cm) and large (≥4 cm) nodules, indicating that monitoring rather than surgery may be appropriate for large biopsy-negative nodules. We investigated the management of thyroid nodules ≥4 cm to determine the proportion of surgeries not necessary for diagnostic purposes and examined for potential predictors. Methods . This was a retrospective cohort study of patients who received a FNA of nodule(s) ≥4 cm between 11/1/2014 and 10/31/2019 at the University of Vermont Medical Center. A surgery was considered unnecessary if the FNA result was benign in the absence of any of the following: compressive symptoms, family history of thyroid cancer in a first degree relative, history of neck irradiation, toxic nodule or toxic multinodular goiter, or substernal extension. Data were analyzed with Wilcoxon rank sum tests, chi square, or Fisher's exact tests. Results . 177 patients had a ≥4 cm nodule during the timeframe and half (54.2%) had surgery. Patients who underwent surgery were significantly younger (51.5 years vs. 62 years; P < 0.001 ), more likely to report obstructive symptoms (34.4% vs. 12.1%; P < 0.001 ) and had a larger nodule size (5.0 cm vs. 4.7 cm; P = 0.26 ). Forty-one patients with benign (Bethesda II) FNA results had surgery, all with negative surgical pathology. Thirteen percentage (23/177) of surgeries were potentially not necessary for diagnostic purposes. Conclusion . Approximately half of our patients with ≥4 cm nodules had surgery, with 13% having surgery not necessary for diagnostic purposes revealing opportunities for improving care and costs.